Arte digital e circuito expositivo: um curto em torno do file - Gasparetto, Débora Aita (2012)
The objective of this research is to discuss the expositive circuit of digital art in contemporaneity, verifying how digital art is articulated, what its particularities are and how it fits in the art circuit. This route is based on the experiences in FILE (Electronic Language International Festival), in the São Paulo 2010 and Porto Alegre 2011 editions, in addition to visits to its virtual environment. This is the most representative event of its kind in Brazil and Latin America, a festival with international projection, which allows discussing the matter. To develop a research about art, it is used a qualitative approach. This is established from a literature survey; field research on spaces in loco and virtual environments of the FILE; interviews with one of the idealizers of the event, Paula Perissinotto, and some artists who have excelled in the course of the festival, among them, Anna Barros, Guto Nobrega and Yara Guasque; in addition to a research by the virtual environments of other spaces and festivals that move the exposition circuit of digital art. Are also conducted visits to some of the major events that discuss the production in Brazil, observing their dissemination strategies and analyzing how they debate, disseminate, exhibit, preserve and commercialize digital art. All these instruments allows to think the digital art in the exposition circuit, reflecting on the observations analyzed around FILE. Thus, the proposal of this dissertation is intended to bring a contribution to the field of history, theory and critical of contemporary art through a study based on recent changes in society, provided by communication, science and technology, which reflects in the relationship between the public, work, artists, institutions and expositive circuits.